1995
DOI: 10.1152/jn.1995.73.2.896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of galvanic vestibular stimulation on human postural responses during support surface translations

Abstract: 1. We investigated the role of the vestibular system in postural control by combining galvanic vestibular stimulation (0.2-0.5 mA) with platform translations in standing subjects. Vestibular stimulation delivered 500 ms before and continuously during the platform translation produced little change in the earliest center of pressure (COP) and center of mass (COM) movements in response to platform translations, but resulted in large changes during the execution of the postural movement and in the final equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 19 publications
5
61
0
Order By: Relevance
“…The major contribution of the vestibular apparatus to posture is in maintaining the whole-body balance by perceiving the changes in direction as well as motion by adjusting the activity of the postural muscles (Inglis, Shupert, Hlavacka, & Horak, 1995;Keshner, Allum, & Pfaltz, 1987). In the normal state, vestibular receptors in each labyrinth generate resting activity; subsequent head movement produces equal and opposite alteration in the activity in each ear.…”
Section: Introductionmentioning
confidence: 99%
“…The major contribution of the vestibular apparatus to posture is in maintaining the whole-body balance by perceiving the changes in direction as well as motion by adjusting the activity of the postural muscles (Inglis, Shupert, Hlavacka, & Horak, 1995;Keshner, Allum, & Pfaltz, 1987). In the normal state, vestibular receptors in each labyrinth generate resting activity; subsequent head movement produces equal and opposite alteration in the activity in each ear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these afferent inputs can provide information regarding load, and thus, have been referred to as load receptors and are particularly useful in signalling COM position (Dietz et al, 1992). Afferent input regarding load may interact with vestibular processing for postural control (Marsden et al 2003) and vestibular input may be important for modulating the magnitude of postural reflexes, particularly for the later recovery responses following surface translations (Inglis et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, while their contributions to gaze stabilization [i.e., vestibuloocular reflex (VOR) ;Angelaki 2004;Cullen 2012;Green and Angelaki 2010a] and postural control (Cathers et al 2005;Horak et al 2001;Inglis et al 1995;Macpherson et al 2007;Stapley et al 2006) have been extensively studied, less is known about the mechanisms by which vestibular signals contribute to voluntary limb control. Classic experiments of Barany in the early 1900s were perhaps the first to demonstrate the influence of vestibular cues on reaching (Barany 1910(Barany , 1912Jones and Fischer 1918).…”
mentioning
confidence: 99%